SPONTANEOUS RUPTURE OF SPLENIC VEIN ANEURYSM - Elshekh, Ahmed Elamin (مجلة الجزيرة للعلوم الصحية; مجلد 5 عدد 2 (2009), 2009)
Spontaneous rupture of splenic vein aneurysm (SVA) is an  extremely rare condition that presents to the emergency department and requires urgent intervention. Preoperative diagnosis is not expected and usually the patient is hemodynamically unstable and there is no time for sophisticated investigations. The important thing is the clinical diagnosis of internal hemorrhage followed by good resuscitation and a thorough laparotomy to know what is going on. Reported cases are very few and most of them were related to pregnancy. Here we report the first case in a single woman which is not related to pregnancy or portal hypertension.